Model of General Government Affairs in Mandau Sub-District, Bengkalis Regency, Riau: Dilemmatic in Planning Preparation - Maulidiah, Sri; Rauf, Rahyunir; Zainal; Rahyunir, Muhammad Hafizh (GoAcademica Research & Publishing, 2024)
Residual affairs, better known as general government affairs (UPU), will be less likely to exist if the more detailed the classification of government affairs. The basis for this research was carried out because the re-emergence of UPU regulations in Law No. 23 of 2014 concerning regional government which previously in Law No. 32 of 2004 was not clearly regulated or even mentioned but appeared to be regulated regarding general government duties (TUP). In practice, UPU in local governments and sub-district governments still has many problems and confusions in implementation, especially related to UPU planning. The purpose of this research is to analyze the implementation of related UPU in the preparation of planning carried out by the Mandau sub-district government, and design the right model related to UPU planning in the sub-district. The approach used in this study is qualitative method of explosive descriptive type. The preparation of the District UPU in planning programs and activities asks for input and proposals from OPD and vertical agencies. In practice, the predetermined planning is submitted to the Regent of Bengkalis to be submitted in the local government work plan which for budgeting is sourced from the APDB which should be submitted to the central government and budgeted through the APBN. The right model in implementing future UPU planning is to make UPU an attributive authority for sub-districts.